Innovations in Artificial Rearing and Mass Production of Beneficial Insects for Biocontrol: A Review - Hurali, Sujay; Narwade, D. K.; Guntupalli, Sravanthi; Sarangi, Satyabrata; Babu, Soumya Bharati; Pandey, Adesh; Thodusu, Mamatha; Patel, Rupendra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The mass production and artificial rearing of beneficial insects have emerged as essential strategies in biological control, offering sustainable alternatives to chemical pesticides in integrated pest management (IPM). The recent innovations in insect mass rearing, focusing on advancements in artificial diet formulations, genetic improvements, automation, and precision agriculture technologies. Traditional rearing methods have faced challenges related to high costs, genetic variability, pathogen contamination, and reduced field performance of artificially reared insects. Cutting-edge biotechnological tools such as CRISPR-Cas9, RNA interference (RNAi), and microbiome engineering have enhanced insect adaptability, resistance to environmental stress, and reproductive efficiency. The implementation of artificial intelligence (AI) and robotics in mass-rearing facilities has optimized environmental conditions, reduced labour costs, and improved quality control. Climate-controlled rearing chambers and sustainable diet formulations incorporating nanotechnology and microencapsulation have significantly enhanced insect fitness, longevity, and field efficacy. The integration of mass-reared beneficial insects with precision agriculture techniques, including drone-assisted releases and GIS-based monitoring, has further increased efficiency and target-specific pest suppression. Despite these advancements, challenges remain, particularly concerning economic viability, regulatory constraints, and ethical considerations associated with large-scale insect production and field release. To address these issues, future research should focus on refining artificial rearing techniques, developing cost-effective rearing systems, and improving genetic diversity in captive insect populations. Strengthening international regulatory frameworks and adopting sustainable mass production practices will be key to the long-term success of biocontrol programs. The potential of artificial rearing technologies to revolutionize pest management, reduce reliance on chemical pesticides, and promote ecological conservation, reinforcing the role of biological control as a cornerstone of modern sustainable agriculture.